Queue time approximation for a single machine with cascading - Lee, Audrey Wan Ling. (2013)
Queueing models have been widely used to evaluate the performance of manufacturing systems. However, due to the trend of rapid growth in regards to the emergence of clustered machines in contemporary manufacturing systems, proper approximation for queueing models have to be derived in order to take the complex tool configurations into account.